A brief review of functionally graded materials - Toudehdehghan A.; Lim J.W.; Foo K.E.; Ma'Arof M.I.N.; Mathews J. (EDP Sciences, 2023)
Beams and girders; Closed form solutions; Engineering applications; Functionally graded material (FGM); Heterogeneous microstructure; Homogenization scheme; Manufacturing process; Material engineering; Spatial coordinates; Functionally graded materials